Butterfly Biodiversity of Jogimatti Forest, Chitradurga, Karnataka- India - Dhananjaya, S. G. (New Visions in Biological Science Vol. 4, 2021)
The objective of the study was to know and estimate the biodiversity of butterflies in the Jogimatti Forest of Chitradurga district, Karnataka, India. As Butterflies from their aesthetic appeal, are good pollinators and highly sensitive to any environmental fluctuation and are considered as good bio-indicators of the health of their habitat. The outcome of survey has revealed presence of 39 species of butterflies belong to 5 family dominated by Nymphalidae (44%), Pieridae (28%), Lycaenidae (13%) Papilionidae (10%) and Hespiridae (5%). With respect to species number and total 430 Nymphalidae (136) and Pieridae (178) butterflies are more. The findings of the study revealed that, Common mormon, Common emigrant, Plain tiger, Common cerulean and Indian cupid are the dominanat butterfly species from their respective families. Jogimatti forest of Chitradurga district has a favourable environmental condition that accommodates butterfly diversity where we can explore more about the host plants responsible for the variety of butterflies.